Dispen-ku Android-Based Application: Assisting Religious Court Judges in Deciding for Marriage Dispensation - Zuhriah, Erfaniah; Mayasari, Lutfiana Dwi; Rahmawati, Erik Sabti; Razak, Abdul Qayuum Bin Abdul; Sukadi, Imam (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
The high rate of child marriage in Indonesia following the marriage dispensation procedure demands an application to help judges decide the proposals accurately and effectively. This 4D development model research aims to create a standard reference in making decisions regarding the dispensation of marriage proposals using an application. The first stage is defining variables used at the application as measurement, the second stage is designing, namely the process of preparing a conceptual framework in the form of technological innovation, the third stage is developing technological innovation and the fourth stage is disseminating, namely the use of an application. At the defining stage, the variables to measure the level of urgency in granting the marriage dispensation include Social, Partnership Role, Financial, Spiritual, and Reproductive or Sexual Readiness. At the designing stage, the Dispen-Ku application is created using Kodular, a website that provides tools for creating Android applications using block programming. In the disseminating stage, the Dispen-ku application which has been uploaded to the Playstore page is distributed to research subjects, namely two judges in Religious Courts.